Answer:
A) horizontal translation; vertical translation
B) H: k = -8; V: k = 16
C: H: g(x) = 2(x +8) -10; V: g(x) = (2x -10) +16; both ⇒ g(x) = 2x +6
Explanation:
Part A:
A linear function can be translated to another linear function by translating it horizontally, vertically, or some combination of those.
- translation right k units: g(x) = f(x -k)
- translation up k units: g(x) = f(x) +k
- translation right h and up k units: g(x) = f(x -h) +k
__
Part B:
Point (x, y) on the graph of f(x) will be translated to point (x+h, y+k) to become a point on the graph of g(x). 'h' is the amount of translation to the right; 'k' is the amount of translation up.
horizontal translation: (x, y) = (5, 0) on f(x) moves to (x +k, y) = (-3, 0) on g(x).
k = -3 -5 = -8 . . . horizontal translation of f(x)
vertical translation: (x, y) = (0, -10) on f(x) moves to (x, y+k) = (0, 6) on g(x).
k = 6 -(-10) = 16 . . . vertical translation of f(x)
__
Part C:
The equation for f(x) has y-intercept -10 and a slope of 2:
f(x) = 2x -10
Horizontal translation using the formula in Part A gives you ...
g(x) = f(x+8) = 2(x +8) -10
Vertical translation gives you ...
g(x) = f(x) +16 = (2x -10) +16
_____
Additional comment
The translated equations simplify to the same thing in both cases:
g(x) = 2x +6